Le commissariat participatif, un pop curating ? Du visiteur électeur au collectionneur médiateur, une expertise négociée - Camart, Cécile (Muséologies, 2026)
The aim is to consider various forms of participatory curating and deliberative democracy practices, in the context of art collections, which have emerged in recent years in France, with a particularly intense focus on contemporary and fine art, as related to three bodies of work that enact dissimilar participatory protocols, sometimes stemming from quite different rationales. While the practice of delegating the curation of art collections has, over the last few decades, been adopted in the form of carte blanche exhibitions, even while accepting the consequences of sometimes radical institutional criticism, it is rarer in the field of contemporary art for curators to agree to transfer their responsibilities to amateurs, to non-professionals, - that is, to those for whom the exhibition is intended: namely, the public, the visitors, the viewers. Protocols vary widely, and are not without impact on assessments of the degree of participation and curatorial co-construction that results. Public involvement was conceptualized in several ways, in considering possible steps toward the creation of conditions for expanding citizen participation in pop curating, providing a framework for long-term advancement toward equality and emancipation. Firstly, limited acts exercised by the voting visitor result at the very least in the decompartmentalization and decanonization of collections, and lead to broader knowledge of museum reserves. With the citizen curator, the feeling of belonging to a group, to a community, and involvement in an ongoing deliberative process as part of this collective, creates the possibility of a fully collaborative curatorial effort. Finally, when collaboration and cooperation become co-creation, through a dual personal and collective contribution on a par with the museum’s functions, the resident-museologist, the collector-mediator, can undoubtedly flourish.